2023
DOI: 10.3390/toxics11020198
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Content in Selected Medicinal Plants Produced and Consumed in Serbia and Their Daily Intake in Herbal Infusions

Abstract: The heavy metals content (HMs) was investigated in 14 different medicinal plants collected from the three regions in Central Serbia, Zlatar, Sokobanja, and Kopaonik. The concentrations of Cd, Cr, Ni, Hg and Pb were determined: Cd (<0.03–2.72 mg/kg); Cr (<0.08–12.1 mg/kg); Ni (<0.08–12.2 mg/kg); Pb (0.6–49.0 mg/kg); the Hg concentration was below the detection limit of 0.06 mg/kg in all samples. The daily intake of HMs due to ingestion of 200 mL of herbal infusion was in all cases below the recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…The results indicated that mean As concentrations for Malawian Moringa in this study ( Table SM1 , Fig. 2 a ) were at least 2-fold lower than those reported in herbs from Bulgaria (range: 0.012–0.225 mg kg −1 ) [4] and Poland (range: 0.120 ± 0.310 mg kg −1 ) [4] , [25] , [26] , [27] , [28] , [29] . Another study conducted by Ahmed et al [30] found As concentrations ranging from 0.040 to 0.126 mg kg −1 in medicinal plants from Pakistan.…”
Section: Resultsmentioning
confidence: 42%
See 1 more Smart Citation
“…The results indicated that mean As concentrations for Malawian Moringa in this study ( Table SM1 , Fig. 2 a ) were at least 2-fold lower than those reported in herbs from Bulgaria (range: 0.012–0.225 mg kg −1 ) [4] and Poland (range: 0.120 ± 0.310 mg kg −1 ) [4] , [25] , [26] , [27] , [28] , [29] . Another study conducted by Ahmed et al [30] found As concentrations ranging from 0.040 to 0.126 mg kg −1 in medicinal plants from Pakistan.…”
Section: Resultsmentioning
confidence: 42%
“…A study conducted in India reported As concentrations ranging from 0.16 to 1.1 mg kg −1 in medicinal plants [31] . Similarly, in a study conducted by Vuong et al [32] , mean As concentrations of 0.343 mg kg −1 , 1.628 mg kg −1 , 0.182 mg kg −1 and 0.295 mg kg −1 in Artemisia vulgaris L., Plantago asiatica L., Eleusine indica (L.) and Phyllanthus urinaria L., respectively [26] , [27] , [28] , [29] , [32] .
Fig.
…”
Section: Resultsmentioning
confidence: 73%